2007
DOI: 10.1016/j.mri.2006.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion MR imaging and proton MR spectroscopic imaging in differentiating necrotizing cerebritis from glioblastoma multiforme

Abstract: We describe a lesion with the magnetic resonance imaging (MRI) characteristics of a glioblastoma mutiforme and demonstrate how perfusion MRI and proton MR spectroscopic imaging can be used to differentiate necrotizing cerebritis from what appeared to be a high-grade glioma. A 43-year-old woman presented to her physician complaining of progressive visual disturbance and headache for several weeks. Conventional MRI demonstrated a parietal peripherally enhancing mass with central necrosis and moderate to severe s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…In an adult case of PCNSA, Pivawer reported that MRSI did not show any rise in choline (Cho) but, rather, an overall decrease in metabolites (Pivawer et al 2007). In pseudotumor PCNSA cases, Panchal and Beppu reported that MRSI was less useful for diagnosis because it displayed a non-specific pattern similar to that of a malignant neoplasm with a significant elevation of choline (Cho) and creatinine (Cr) peaks suggesting respectively an increased cell turnover and an energy-dependent system.…”
Section: Findings On Functional Imagingmentioning
confidence: 99%
See 4 more Smart Citations
“…In an adult case of PCNSA, Pivawer reported that MRSI did not show any rise in choline (Cho) but, rather, an overall decrease in metabolites (Pivawer et al 2007). In pseudotumor PCNSA cases, Panchal and Beppu reported that MRSI was less useful for diagnosis because it displayed a non-specific pattern similar to that of a malignant neoplasm with a significant elevation of choline (Cho) and creatinine (Cr) peaks suggesting respectively an increased cell turnover and an energy-dependent system.…”
Section: Findings On Functional Imagingmentioning
confidence: 99%
“…The wide spectrum of protean clinical signs is related to ischemia which affects any part of the brain and can be micro-or macroscopic, focal, multifocal or diffuse. It contrasts with the paucity of extraneurologic signs and the preserved general state, at least at the beginning of the disease's evolution (Younger 2004;Rosenbaum et al 1998;Soloman et al 2000;Hajj-Ali et al 2002;Zuber 2005;Noskin et al 2006;Calabrese et al 2007;Pivawer et al 2007). All the combinations between the various following manifestations are possible, but the triad of headache, organic brain syndrome, and multifocal neurologic deficits is most suggestive (Salvarani et al 2007(Salvarani et al , 2008a: -Headache (63%), typically persistent, insidious and progressive, sometimes accompanied by other signs of intracranial hypertension with nausea and vomiting; -Diffuse encephalopathy signs including altered cognitive function (50%) and amnestic syndrome (9%); -Focal neurological signs including:…”
Section: Clinical Signsmentioning
confidence: 99%
See 3 more Smart Citations